Recurrent Incisional Hernia due to Pseudomyxoma Peritonei - Zafer Ergul; Engin Olcucuoglu; Hakan Kulacoglu; Cenap Dener (Case Reports in Medicine)
Pseudomyxoma peritonei is a rare but challenging neoplastic disease which is characterized with intraperitoneal mucinous-gelatinous fluid accumulation. It rarely presents as a mass mimicking abdominal wall hernias A recurrent incisional hernia due to pseudomyxoma peritonei is presented here. A 60-year-old female patient had been operated on for a left mucinous ovarian cyst 20 cm in diameter in 1998. Mucinous material had disseminated into interloop spaces through the right subdiaphragmatic region. Total abdominal hysterectomy + bilateral salpingooophorectomy and peritoneal toilet had been performed. She was rehospitalized for abdominal distention and a 4 cm defect over the incision and underwent a hernia repair using polypropylene mesh in 2001. Abdominal distention recurred to give a rise to an incisional hernia in 2006. She was reoperated for decompression and repair, but nothing could be done because of sticky adhesions and the incision were simply closed. The patient was referred to our department for operation. A prosthetic hernia repair with 30×30 cm polypropylene mesh was performed. The patient was discharged on the postoperative 5th day following an uneventful recovery. However, she died of disseminated disease after 18 months.